2009
DOI: 10.3354/meps07972
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemistry of a deep-sea whale fall: sulfate reduction, sulfide efflux and methanogenesis

Abstract: Present address: Bundesanstalt für Geowissenschaften und Rohstoffe, Stilleweg 2, 30655 Hannover, GermanyABSTRACT: Deep-sea whale falls create sulfidic habitats supporting chemoautotrophic communities, but microbial processes underlying the formation of such habitats remain poorly evaluated. Microbial degradation processes (sulfate reduction, methanogenesis) and biogeochemical gradients were studied in a whale-fall habitat created by a 30 t whale carcass deployed at 1675 m depth for 6 to 7 yr on the California … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
169
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(189 citation statements)
references
References 67 publications
11
169
1
2
Order By: Relevance
“…Extensive microbial degradation and low scavenging activity were reported at large, deep-sea jelly-fall deposits ( jelly-detritus cover 100% of the seafloor) in the Gulf of Oman [12] and at large deep-sea pysosome deposits discovered off Ivory Coast [13] and the continental slope off the eastern US coast [21,22]. The difference between our study and these other observations could be related to differences in the sizes of the jelly-fall deposits between studies, with high concentrations of dissolved inorganic carbon (DIC), noxious sulfide and ammonium produced at large jelly-fall deposits deterring scavengers from feeding [14,26,27]. However, the small size of jelly falls in this study does not appear to be the main reason for the rapid scavenging activity observed as comparatively little or a complete lack of scavenging has also been observed at small gelatinous deposits in the deep Gulf of Oman (approx.…”
Section: Discussioncontrasting
confidence: 55%
“…Extensive microbial degradation and low scavenging activity were reported at large, deep-sea jelly-fall deposits ( jelly-detritus cover 100% of the seafloor) in the Gulf of Oman [12] and at large deep-sea pysosome deposits discovered off Ivory Coast [13] and the continental slope off the eastern US coast [21,22]. The difference between our study and these other observations could be related to differences in the sizes of the jelly-fall deposits between studies, with high concentrations of dissolved inorganic carbon (DIC), noxious sulfide and ammonium produced at large jelly-fall deposits deterring scavengers from feeding [14,26,27]. However, the small size of jelly falls in this study does not appear to be the main reason for the rapid scavenging activity observed as comparatively little or a complete lack of scavenging has also been observed at small gelatinous deposits in the deep Gulf of Oman (approx.…”
Section: Discussioncontrasting
confidence: 55%
“…Similar to gas seeps representing conspicuous oases of sedimentary activity, dense organic matter deposits at the seafloor, such as animal carcasses (Fig. 4B) and wood falls, also support microbial and faunal communities that are more active than those in surrounding sediments (29,194,503,504,564). Where such "food falls" occur, a succession of microbial and macrofaunal communities colonize the deposit, and high levels of biological activity result (194).…”
Section: General Physical and Chemical Characteristicsmentioning
confidence: 99%
“…Where such "food falls" occur, a succession of microbial and macrofaunal communities colonize the deposit, and high levels of biological activity result (194). The influx of more labile organic carbon to the sediment leads to an increase in sediment microbial activity and the development of shallow sulfate reduction zones in the sediment (564).…”
Section: General Physical and Chemical Characteristicsmentioning
confidence: 99%
“…It has been estimated that > 50 % in spring (FebruaryMarch), < 25 % in summer (July-August), and > 75 % in autumn (September-October) of these blooms is reaching the seafloor (Smetacek et al, 1984), resulting in an overall high organic carbon content of the sediment (5 wt %), which leads to high benthic microbial degradation rates including sulfate reduction and methanogenesis (Whiticar, 2002;Treude et al, 2005a;Bertics et al, 2013). Previous studies revealed that high organic matter availability can relieve competition between sulfate reducers and methanogens in sulfatecontaining marine sediments (Oremland et al, 1982;Holmer and Kristensen, 1994;Treude et al, 2009;Maltby et al, 2016). To determine the effect of POC concentration and C / N ratio (the latter as a negative indicator for the freshness of POC) on SRZ methanogenesis, two PCAs were conducted with (a) the focus on the upper 0-5 cm b.s.f., which is directly influenced by freshly sedimented organic material from the water column (Fig.…”
Section: Particulate Organic Carbonmentioning
confidence: 99%